2012
DOI: 10.1007/s10973-012-2721-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved dehydrogenation/rehydrogenation performance of LiBH4 by doping mesoporous Fe2O3 or/and TiF3

Abstract: The LiBH 4 ? mesoporous Fe 2 O 3 (defined as M-Fe 2 O 3 ) mono-doped and LiBH 4 ? M-Fe 2 O 3 ? TiF 3 codoped hybrid materials were prepared by ball milling process. A variety of characterization methods, such as thermogravimetric, differential scanning calorimetry, X-ray diffraction, and pressure-composition-temperature instrument, were used for examinations of the two materials' performances of storage/release of hydrogen, catalytic activity, kinetics, and thermodynamics. All the results showed that the M-Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…63 The cyclic stability of bulk LiBH 4 −CaH 2 has also been reported by Li. 64 Bulk LiBH 4 −CaH 2 decreases in capacity by 66% during 10 desorption cycles with rehydrogenation conditions of 450 °C under 8 MPa for 16 h and with dehydrogenation performed at 450 °C under 0.1 MPa H 2 pressure. In comparison to our results, 450 °C is insufficient to obtain stable reversibility of LiBH 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…63 The cyclic stability of bulk LiBH 4 −CaH 2 has also been reported by Li. 64 Bulk LiBH 4 −CaH 2 decreases in capacity by 66% during 10 desorption cycles with rehydrogenation conditions of 450 °C under 8 MPa for 16 h and with dehydrogenation performed at 450 °C under 0.1 MPa H 2 pressure. In comparison to our results, 450 °C is insufficient to obtain stable reversibility of LiBH 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…To our knowledge, no studies have been reported on LiAlH 4 doped with Fe 2 O 3 and Co 2 O 3 . According to Zhang et al, mesoporous Fe 2 O 3 exhibits a prominent effect on improving the dehydrogenation properties of LiBH 4 . Recently, it has also been reported that Fe 3+ and Fe could provide favorable effect on enhancing the dehydrogenation properties of LiAlH 4 . , Thus, Fe 2 O 3 could be selected as catalyst precursor to investigate its effect on the dehydrogenation properties of LiAlH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental studies involving LiBH 4 with transition metal oxides have been reported for hydrogen storage applications. 27–29 Zhang and his co-workers 30 reported that the re-hydrogenated (at 400 °C under 4.5 MPa) LiBH 4 /M-Fe 2 O 3 /TiF 3 system absorbed ∼4.27 wt% of hydrogen within 60 minutes. In a previous study, ∼1.7 wt% hydrogen uptake capacity for LiBH 4 –2LiNH 2 -0.05/3Co 3 O 4 systems was found under rehydrogenation conditions of 25–220 °C and 110 bar H 2 pressure.…”
Section: Introductionmentioning
confidence: 99%